Gas phase synthesis of dimethyl carbonate from CO2 and CH3OH over Cu-Ni/AC. A kinetic study (2020)
The catalytic activity for dimethyl carbonate formation from carbon dioxide and methanol over mono and bimetallic Cu:Ni supported on activated carbon is presented. Bimetallic catalysts exhibit higher catalytic activity than the monometallic samples, being Cu:Ni-2:1 (molar ratio) the best catalyst; X-Ray diffraction, transmission electron microscopy, and metal dispersion analysis provided insight into the improved activity. In situ FT-IR experiments were conducted to investigate the mechanism of formation of dimethyl carbonate from methanol and carbon dioxide over Cu-Ni:2-1. The kinetics of the direct synthesis of dimethyl carbonate in gas phase over Cu:Ni-2:1 supported on activated carbon catalyst was experimentally investigated at 12 bar and temperatures between 90 °C and 130 °C, varying the partial pressures of CO2 and methanol. Experimental kinetic data were consistent with a Langmuir-Hinshelwood model that included carbon dioxide and methanol adsorption on catalyst actives sites (Cu, Ni and Cu-Ni), and the reaction of adsorbed CO2 with methoxi species as the rate determining step. The estimated apparent activation energy was 94.2 kJ mol-1. ©2019.